POPULASI LUTUNG SENTARUM (Presbytis chrysomelas cruciger) DI RESORT SEMANGIT TAMAN NASIONAL BETUNG KERIHUN-DANAU SENTARUM - Nurida, Nurida; Darwati, Herlina; Rifanjani, Slamet; Arini, Wahyuningyan; Santoso, Nyoto; Sutopo, Sutopo (JURNAL HUTAN LESTARI, 2024)
Langur Sentarum is a species of Langur endemic from borneo which has an endangered status but has not been included in the list of legally protected species in Indonesia. This is due to the lack of data regarding the Langur Sentarum, especially data regarding the population. The purpose of this study was to record the Langur Sentarum population. Methods of data collection by purposive sampling. Population is calculatated using concentration count and record the number of individuals, age structure and sex. The population results obtained were 7 groups totaling 51 individuals. The age structure is 25 adults, 19 adolescens and 7 children with a sex ratio of 1 : 2,57 in the adult category and 1 : 1,38 in the adolescent category. The existence and well-being of the Langur Sentarum group can be caused by factors of habitat conditions, vegetation, and human presence. Keywords: BKDNP, Langur Sentarum, population Abstrak Lutung Sentarum merupakan jenis Lutung endemik kalimantan yang memiliki status terancam punah namun belum masuk kedalam daftar satwa yang dilindungi secara hukum di Indonesia. Hal tersebut disebabkan kurangnya data mengenai Lutung Sentarum, salah satunya data mengenai populasi. Tujuan penelitian ini adalah untuk mendata populasi lutung sentarum. Metode pengambilan data secara purposive sampling. Populasi dihitung dengan concentration count dan mencatat jumlah individu, struktur umur dan jenis kelamin. Hasil populasi yang didapatkan adalah 7 kelompok dengan total 51 individu. Struktur umur yaitu 25 individu dewasa, 19 individu remaja dan 7 individu anak dengan sex ratio 1 : 2,57 pada kategori dewasa dan 1 : 1,38 pada kategori remaja. Keberadaan dan kesejahteraan kelompok Lutung Sentarum dapat disebabkan oleh faktor kondisi habitat, vegetasi, dan keberadaan manusia. Kata kunci: TNBKDS, Lutung Sentarum, populasi